2003
DOI: 10.1520/gtj11326j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matric Suction on the Results of Plate Load Tests Performed on a Lateritic Soil Deposit

Abstract: The performance of foundation systems on unsaturated soil deposits is considerably influenced by variations of the negative pore-water pressure (i.e., matric suction) distribution within the soil mass due to local microclimate conditions. Although significant understanding has been gained in the last few decades on the behavior of unsaturated soils, the use of unsaturated soil mechanics concepts in the interpretation of field tests has not been incorporated into the state-of-practice. As a consequence, conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Second, there is a lack of a valid framework to interpret bearing capacity and settlement behaviour of unsaturated soils. Steensen-Bach et al (1987), Oloo et al (1997), Costa et al (2003), Mohamed and Vanapalli (2006), Rojas et al (2007), and demonstrated that the bearing capacity of unsaturated soils is significantly influenced by matric suction from their investigations on model footing or in situ plate load tests. Recently, Vanapalli and Mohamed (2007) provided a framework to both interpret and predict the variation of bearing capacity of unsaturated soils with respect to matric suction using saturated shear strength parameters (i.e., c', f 0 ) and the soil-water characteristic curve (SWCC).…”
Section: Introductionmentioning
confidence: 99%
“…Second, there is a lack of a valid framework to interpret bearing capacity and settlement behaviour of unsaturated soils. Steensen-Bach et al (1987), Oloo et al (1997), Costa et al (2003), Mohamed and Vanapalli (2006), Rojas et al (2007), and demonstrated that the bearing capacity of unsaturated soils is significantly influenced by matric suction from their investigations on model footing or in situ plate load tests. Recently, Vanapalli and Mohamed (2007) provided a framework to both interpret and predict the variation of bearing capacity of unsaturated soils with respect to matric suction using saturated shear strength parameters (i.e., c', f 0 ) and the soil-water characteristic curve (SWCC).…”
Section: Introductionmentioning
confidence: 99%
“…where B is the width of the foundation; L is the length of the foundation; and N unsat is the UBC factor in unsaturated soils, which was obtained using back analysis by Oh and Vanapalli (2013) [18]. In addition, for the estimation of the UBC of foundations on coarse-grained unsaturated soils under drained loading conditions, equations based on the modification of the UBC equation (Equation ( 4)) proposed by Terzaghi (1943) [1] for strip foundations on saturated soils is available in the literature [12,13,15,26,29,30,32,34].…”
Section: Estimation Of Ubc Of Foundations On Unsaturated Soilsmentioning
confidence: 99%
“…Therefore, research on the behavior of unsaturated soils has been prioritized over the last ten years. In the literature, experimental studies have been conducted under both drained and undrained conditions [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In general, research in this area has aimed to improve understanding of the mechanical behavior of unsaturated soils and to develop appropriate methods for assessing the bearing capacity of unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have covered several of these problems (11)(12)(13)(14)(15)(16)(17), including programs to establish the mechanical, strength, and physical properties of soils (12,(18)(19)(20), relationships between various physical and mechanical test methods (15,(21)(22)(23), variables affecting different test methods (24)(25)(26)(27)(28)(29), design philosophies (30), quality control and assurance in construction (25,31), and so forth. Soil stabilization with lime is widely accepted for improving problematic soils like clay in subgrade engineering (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%